PROBLEMATIC INTERNET USE PADA REMAJA: ANALISIS BIBLIOMETRIK - Andrianie, Prilya Shanty; Purwandari, Eny; Taufik, Taufik (Universitas Gunadarma, 2024)
Apart from providing various conveniences, excessive internet use can also have negative impacts, one of which is problematic internet use (PIU). This research aims to find out studies regarding problematic internet use in teenagers so that further research can be carried out. The research method used is a biometric analysis using VOSviewer on published articles indexed by Scopus from 2018 to 2023. The research results show that searching journals on the scopus.com site with the keyword